A novel superchilling storage – ice glazing (SS‐IG) approach using biopolymer‐based composite hydrogel to delay microbiological spoilage and organic oxidation of preserved tilapia. (22nd May 2018) - He, Qi; Gong, Bin; He, Jiapeng; Yang, Xiaocui; Xiao, Kaijun; Zhu, Liang
Abstract: Background: Most aquatic products are highly susceptible to deterioration and microbial spoilage during storage. Cold storage is a frequently used method to preserve them. However, products preserved by traditional frozen method are prone to suffer damage. This can significantly impair the quality of the products. To solve the problem, this work established a novel superchilling storage‐ice glazing (SS‐IG) approach using chitosan‐catechin composite material. It can maximize the postmortem quality of preserved products during storage, avoiding damage. Results: During storage at −1.5 ± 0.2 °C for 25 days, the SS‐IG approach using 5 g L −1 chitosan and 1∼3 g L −1 catechin as IG layers can effectively enhance the postmortem quality of preserved tilapia fillets. The sensory qualities of these fillets were effectively maintained. The microbial counts in these fillets were strongly suppressed. Oxidative rancidity in these fillets was observably inhibited. Less biogenic amine was produced in these fillets. Conclusion: The results indicated that the SS‐IG with chitosan‐catechin composite‐ice glazing layers can be effective in maintaining the postmortem quality of tilapia fillets. This will have a wide potential application. © 2018 Society of Chemical Industry